Analisis Cerpen Ahmad Tohari dalam Judul “Rumah yang Terang - Dani Maulana; Fajar Muhammad Fadlillah (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2022)
One of Ahmad Tohari's short stories is The Bright House, in the collection of short stories Smile Karyamin (2013). The short story records the incident of electricity entering a village. As narrated in the short story, the existence of electricity has a significant impact on society, both positively and negatively. The positive side brings physical changes with the presence of lights and other facilities to support people's lives. On the other hand, this positive aspect has a negative impact, namely the